ANALISIS PERBANDINGAN MANAJEMEN OPERASIONAL PT. INDOBANGKIT PERTAMA SUKSES SEBELUM, SELAMA DAN SETELAH PANDEMI COVID-19 - Fendy Cuandra; Shereen; Jennifer; Rico Kartono; Cindy; Sun Bhuan (Transpublika Publisher, 2023)
PT Indobangkit Pertama Sukses is a manufacturing company that has been operating since 2016. It specializes in plastic manufacturing, producing Assoy Plastic, Meebag, Thinpack, PVC Rope, and T-bag. This research analyzes the operational management of PT Indobangkit Pertama Sukses before, during, and after the COVID-19 pandemic using qualitative data gathered through observation and interviews (conducted via Zoom Meeting) with operational managers. The research was conducted in Batam, where the company is located. The findings show that PT Indobangkit Pertama Sukses involves many parties and requires good product and information flow. The SCM concept can help the company plan production schedules and raw material supply to produce high-quality products. PT Indobangkit Pertama Sukses manages inventory and forecasting management well, achieving a large turnover. The company has carried out Planning, Scheduling, and Controlling in every activity and overcomes the obstacles of production machines that often break down.